A correlative study of body mass index with oxidative stress parameters (serum uric acid and serum malondialdihyde) in essential hypertension - Shrivastav, Chanchal; Parekh, Paras Arvindbhai; Kumar, G. Indra (International Journal of Research in Medical Sciences, 2019)
Background: Hypertension is most commonly documented modifiable risk factor for cardiovascular diseases. A growing body of data proposes an appreciated pathogenic role of an elevated serum uric acid in atherosclerosis and cardiovascular disease (CVD). Increased oxidative stress could be involved in the pathogenesis of hypertension. Oxidative stress marker, serum uric acid (SUA) and serum malondialdyhyde level (S. MDA) are affected by both genetic and environmental factors and related to biological factors as gender, age and body mass. So, the aim of the study is to access the association of body mass index (BMI) with oxidative stress parameters in essential hypertension (EHT). Methods: For the said purpose, this case control study was carried out on a total of 200, age and sex matched 75 hypertensives, 75 prehypertensive and 50 healthy subjects. After diagnosis of cases, SUA was estimated by standard kit method and S. MDA was estimated manually by Buege and Aust method. Results: This study represents that systolic and diastolic blood pressure were increased with increased BMI in all groups. Oxidative stress marker, SUA and S. MDA level increased significantly with increasing BMI in all groups and were positively correlated. Conclusions: Our study indicates that monitoring of the blood pressure, SUA and S. MDA at regular interval and maintaining of the oxidative balance would be helpful in preventing the development of hypertension and associated cardio-vascular morbidities.